The bushmeat trade in traditional markets in North Sulawesi, Indonesia - TILTJE ANDRETHA RANSALELEH; INDYAH WAHYUNI; MERRI DIANA ROTINSULU; MEIS JACINTA NANGOY; AGUSTINUS LOMBOAN; JANE ONIBALA; SYLVIA LAATUNG; LIDYA SIULCE KALANGI; SURYO SAPUTRO; SIGIT WIANTORO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Ransaleleh TA, Wahyuni I, Rotinsulu MD, Nangoy MJ, Lomboan A, Onibala J, Laatung S, Kalangi LS, Saputro S, Wiantoro S. 2025. The bushmeat trade in traditional markets in North Sulawesi, Indonesia. Biodiversitas 26: 1929-1939. The bushmeat trade, which involves harvesting wild animal meat, is causing significant changes in the ecological balance of flora and fauna, with potential implications for human health and well-being. Traditional markets in several districts and cities in North Sulawesi Province, Indonesia, serve as centers for the bushmeat trade. Therefore, this study aimed to inventory and map the locations of market centers for bushmeat trade, provide current data, and monitor the types of endemic wild animals that are protected but are used as food in North Sulawesi. Hence, 11 markets were surveyed, namely Dumoga, Imandi, Ibolian, Amurang, Motoling, Kawangkoan, Langowan, Beriman, Airmadidi, Bersehati, and Pinasungkulan. Direct observations were implemented in each market every month from April to September 2024. The obtained data were then identified, tabulated, analyzed, and described in a descriptive manner. The results showed that the types of traded bushmeat were wild boar, bats, white-tailed forest rats, rice field rats, Sulawesi bear cuscus, Small Sulawesi cuscus, weris birds, and rice field snakes. Two species of cuscus are endemic to Sulawesi and adjacent islands and are listed as threatened species under the IUCN Red List. Moreover, the small Sulawesi cuscus is protected under Indonesian regulations. The two species of bats identified were Acerodon celebensis and Styloctenium wallacei, both of which are endemic to Sulawesi and listed as threatened species under the IUCN. Our observation showed that bushmeat trade was. Found in all 11 traditional markets in North Sulawesi, providing endemic and non-endemic and, as well as protected species under government regulation. Further conservation interventions are needed, including law enforcement strategies, education, and public awareness about the role of wild animals in providing ecosystem services and maintaining ecological balance in the surrounding environment.